A Lucknolide Derivative Induces Mitochondrial ROS-Mediated G2/M Arrest and Apoptotic Cell Death in B16F10 Mouse Melanoma Cells - Jae Hyeop Lee; Byeoung-Kyu Choi; Minsoo Kim; Hee Jae Shin; Sun Joo Park (Marine Drugs)
Melanoma is an aggressive skin cancer with a high risk of cancer-related deaths, and inducing apoptosis in melanoma cells is a promising therapeutic strategy. This study investigates the anti-tumor potential of a novel lucknolide derivative LA-UC as a therapeutic candidate for melanoma. Lucknolide A (LA), a tricyclic ketal-lactone metabolite isolated from marine-derived Streptomyces sp., was chemically modified by introducing a 10-undecenoyl group to synthesize LA-UC. LA-UC preferentially inhibited the proliferation of melanoma cells, including B16F10, while exerting minimal effects on normal melanocytes or other tumor cell types, indicating the selective action of LA-UC against melanoma cells. LA-UC decreased G2/M checkpoint proteins, including cyclin B1 and Cdc2, while activating caspase-3 and caspase-9, resulting in G2/M cell cycle arrest and inducing apoptotic cell death in B16F10 cells. The addition of a pan-caspase inhibitor confirmed the caspase-dependent mechanism of LA-UC-induced cell death. Additionally, LA-UC elevated mitochondrial ROS levels, leading to mitochondrial membrane disruption, upregulation of pro-apoptotic proteins, and DNA damage in melanoma cells. The ROS scavenger N-acetylcysteine reduced LA-UC-induced mitochondrial ROS accumulation, mitochondrial membrane disruption, DNA damage, and apoptosis. Collectively, these findings suggest that LA-UC induces G2/M cell cycle arrest and caspase-dependent apoptosis in B16F10 cells through excessive mitochondrial ROS generation, membrane impairment, and DNA damage, highlighting its potential as a promising therapeutic candidate for melanoma treatment.